Maternal-Fetal Conflict: A Call for Humanism and Consciousness in a Time of Crisis - Amana, Cheryl E. (Columbia Journal of Gender and Law, 1992)
This Article examines state intervention in the life of the pregnant woman whereby medical treatment is imposed upon her over her objection. It focuses specifically on obstetrical intervention and the fundamental danger of using this intervention coercively in an attempt to regulate a woman’s medical care, lifestyle, and personal decisions during the course of her pregnancy. This Article suggests that the woman, to the extent that she is competent, is the appropriate decision maker regarding medical care for her fetus. To decide otherwise. violates the woman’s right to make informed choices and to give informed consent, two of the underlying principles supporting autonomy in decision making about medical care. Moreover it impugns her constitutional right to bodily integrity.